Effect of Over-Wintering on Three Cyprinid Fish Raised in Earthen Ponds in Basra Province, Southern Iraq - Yesser et al. (Iraqi Journal of Aquaculture, 2025)
This study aimed to evaluate the effect of winter conditions and restricted feeding on the growth performance of three cyprinid species, common carp (Cyprinus carpio), grass carp (Ctenopharyngodon idella), and silver carp (Hypophthalmichthys molitrix) reared in earthen ponds in Basra Province, southern Iraq. The trial was conducted during the winters of 2015, 2016, and 2017 in two ponds at the Marine Science Center, each stocked at a density of 5000 fish/ha with a species composition of 50% common carp, 30% grass carp, and 20% silver carp. Fish were fed only on natural food with no supplementary feeding. Water temperatures ranged from 9.2°C to 18.1°C across the studied winters. Growth performance, evaluated through weight gain and specific growth rate (SGR), varied among species and years. The highest SGRs for common carp, grass carp, and silver carp were recorded in 2016 at 0.719, 1.195, and 2.355% g/day, respectively. Gross production peaked in 2017, reaching 705 kg/ha/90 days for common carp and 265 kg/ha/90 days for silver carp. The findings suggest that winter rearing under restricted feeding may result in acceptable growth rates, particularly for silver carp, and can reduce operational costs. Implementing such feeding strategies may optimize fish production by lowering labor and feeding input during colder months.